Aerosol jetting of Bi2Te3 nanowires for flexible thermoelectric applications - Sia, Seng Ann (Nanyang Technological University, 2023)
This project investigates the use of Aerosol Jet technology for printing Bi2Te3 nanowires on a flexible substrate for waste heat applications. The flexibility of the substrate enables better contact with heat sources, addressing the challenge of establishing good contact with irregularly shaped heat sources in current thermoelectric devices. n- and p-type Bi2Te3 nanowires were synthesized through a two-step process involving the growth of ultrathin tellurium nanowires followed by the diffusion of bismuth. The synthesized nanowires were made into ink solutions for aerosol jet printing, with various printing parameters explored. The nanowires were visualized on the substrate using SEM, and their thermoelectric properties were measured using ZEM-3. The report concludes with a discussion of the results, highlighting the successful synthesis and printing of Bi2Te3 nanowires on a flexible substrate, and recommendations for future research.